1998
DOI: 10.1021/om980753i
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Diphenylphenyl-Based Organometallic Compounds of Gallium

Abstract: (2,6-Diphenylphenyl)lithium−bis(diethyl ether), Ph2C6H3Li·2Et2O (I), was synthesized by reaction of n-butyllithium with 2,6-diphenyl-1-iodobenzene in diethyl ether. Reaction of I with group 13 metal halides, MX3 (M = Ga, X = Cl, I; M = In, X = Cl), affords bis(2,6-diphenylphenyl)gallium iodide, (Ph2C6H3)2GaI (II), bis(2,6-diphenylphenyl)indium chloride, (Ph2C6H3)2InCl (III), and bis(diethyl ether)lithium trichloro-2,6-diphenylphenylgallate, [Li·2Et2O][Ph2C6H3GaCl3] (IV). Reaction of (2,4,6-triphenylphenyl)lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…from an amine to an ether, a change in value is expected, in accord with the observations made previously for the CpLi complexes. The diethyl ether (DEE) complexes of 2,6-diphenylphenyllithium 13 and 2,4,6-triphenylphenyllithium 14 (5 and 4, respectively) are both LiAS 2 systems, with the lithium cation tricoordinated. These two complexes have values of 310 and 308 kHz, respectively.…”
Section: Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…from an amine to an ether, a change in value is expected, in accord with the observations made previously for the CpLi complexes. The diethyl ether (DEE) complexes of 2,6-diphenylphenyllithium 13 and 2,4,6-triphenylphenyllithium 14 (5 and 4, respectively) are both LiAS 2 systems, with the lithium cation tricoordinated. These two complexes have values of 310 and 308 kHz, respectively.…”
Section: Monomersmentioning
confidence: 99%
“…13 C. If it can be assumed that there are no fast dynamic processes present, i.e. exchanges, and that the rearrangement of the q zz and 13 C-1 H internuclear vectors are exactly the same, the QSC value is given by the equation 9a QSC D 70.0[T 1 13 C /T 1 7 Li ] 1/2 2 QSC values of some phenyllithium complexes have been reported previously and it was found that this parameter could be used to deduce the aggregation state of these complexes in solution.…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state structure of bis(2,6-diphenylphenyl)gallium iodide, (2,6-Ph 2 C 6 H 3 ) 2 GaI, 16 displays the gallium atom in a somewhat distorted trigonal planar environment (C-Ga-C: 134.3(3)…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Whereas for R ϭ mesityl (16) [38] the structure is based on a normal (CLi) 2 core, for the more sterically congested ligand in which R ϭ 2,6-(iPr) 2 C 6 H 4 (17) dimerisation occurs by the η 6 -interaction of one R group on each ligand with the metal component of an adjacent monomer. [39] Solvated analogues exhibit even more diverse behaviour; 2,6-(C 10 H 7 ) 2 C 6 H 3 Li·2THF (18), [40] 2,6-Ph 2 C 6 H 3 Li·2OEt 2 (19), [41] 2,6-[4-(tBu)C 6 H 4 ] 2 C 6 H 3 Li·2OEt 2 (20), [42] 2,6-(4-MeOC 6 H 4 ) 2 C 6 H 3 Li·2OEt 2 (21) (wherein the methoxy groups are passive with respect to the metal), [43] 2,6-[2,4,6-(iPr) 3 C 6 H 2 ]C 6 H 3 Li·L (L ϭ OEt 2 22, [44] η 6 -C 6 H 6 23 [39] ) and 2,4,6-Ph 3 C 6 H 2 Li·2OEt 2 (24) [45] are monomers in the solid state while 2,4,6-(iPr) 3 C 6 H 2 Li·OEt 2 (25) [46] and 2,4,6-Me 3 C 6 H 2 Li·2THF (26) [47] form differently solvated dimers. The complex 2,4,6-Ph 3 structure straddle the formal charge centres, one is mono-THF solvated and the other is bis(η 2 -Ph) supported.…”
Section: Solid-state Studiesmentioning
confidence: 99%
“…15) [37] to yield µ 2 -biphenyl sulfide-C2,C2, C2Ј,C2Ј-bis(lithium-TMEDA) (40). [56] In the context of ''SϩO class'' directing agents, 3-fluorophenyl(phenyl)sulfone has been shown to undergo lithiation on the fluorinated ring between the two substituents to afford 3-FC 6 H 3 (Li·PMDETA-2)SO 2 Ph (41). [57] Of the two possible coordinating substituents, it is the SO 2 moiety that dominates, with one of its two oxygen centres interacting with the metal [LiϪO ϭ 2.170(8) Å ; Li···F ϭ 3.672(7) Å ].…”
Section: Solid-state Studiesmentioning
confidence: 99%